The determinants of capital structure : the impact of the 2008 financial crisis on the Portuguese and Spanish SMEs - Lousan, João de Sousa Pereira Cubeles (2017)
The capital structure and what determines it, has been one of the most, discussed subjects in the corporate finance world, mainly since the contribution of Modigliani and Miller (1958). Empirical works on this subject are mainly focus on large firms capital structure with only a few more recent works focusing on the capital structure of small and medium enterprises (SMEs). The financial crisis of 2008 caused by the subprime crisis led to a a credit crunch leaving small firms with their access to financing restrained. Therefore, this work provides evidence on how the Portuguese and Spanish SMEs dealt with that restrained credit access, analysing the differences between the two countries and between the periods before, during and after the crisis Hence, we verify that although the level of external financing of SMEs in both countries was negatively affected by the crisis, the choice between financing sources proved to be the same throughout the periods and identical between Portugal and Spain. From an unbalanced panel data analysis of 17 814 Portuguese SMEs and 61 688 Spanish SMEs we examine some of the determinant of capital structure defined by previous theories, assets tangibility, non-debt tax shields, growth opportunities, firm’s uniqueness, size and profitability, we find strong support for the pecking order theory as the best theory explaining SMEs financing decisions, with profitability having the highest influence on firms’ leverage.